EFEKTIVITAS MENINGKATKAN PENJUALAN PRODUK PENYANDANG DISABILITAS MENGGUNAKAN MEDIA FACEBOOK: EFFECTIVENESS OF INCREASING SALES OF PRODUCTS FOR PEOPLE WITH DISABILITIES USING FACEBOOK MEDIA - ST Hajar Munawarah; Indri Anugrah Ramadhani; Matahari (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
People with disabilities in Indonesia continue to face significant challenges in developing their businesses, particularly in product marketing. This study aims to examine the effectiveness of Facebook utilization training and mentoring in improving the sales performance of micro, small, and medium enterprises (MSMEs) operated by people with disabilities in Sorong Regency. The study employed a quantitative approach using a quasi experimental design with a one-group pretest–posttest design, involving 20 MSME entrepreneurs with disabilities. Data were collected through a closed-ended questionnaire using a four-point Likert scale, measuring six indicators: promotion intensity, market reach, transaction convenience, income, independence, and self confidence. The results of the paired sample t-test revealed a statistically significant difference between pretest and posttest scores (t = −3.525, p = 0.002). The highest improvements were observed in transaction convenience (0.90 points), income (0.65 points), and self-confidence (0.50 points). The normalized gain value of 0.35 indicates a moderate level of program effectiveness, with 42.1% of participants achieving a high effectiveness category. This study concludes that Facebook utilization training and mentoring are effective in enhancing the business performance of MSMEs operated by people with disabilities; however, continuous post-training mentoring is necessary to optimize outcomes for all participants. The findings highlight the importance of practical, measurable training programs supported by sustained mentoring to promote inclusive and sustainable digital entrepreneurship